Beginning Reading Ability Using the Method Synthetic Structural Analytics (SAS) - Renni Ramadhani Lubis; Siti Irene Dwiningrum; Enny Zubaidah (Prodi PGMI IAIN Salatiga, 2021)
This study aims to describe a literature review on early reading skills using the method synthetic structural analysis (SAS)in grade 1 students at Madrasah Ibtidaiyah Negeri 2 Langkat. This study uses a qualitative research method with a literature review approach. The research stages were carried out by means of article collection, article reduction, article display, discussion and conclusion. Sources of research data are international and national journal articles in 2015-2021. The results showed that from 25 articles, 13 articles were found that matched the topic title. Beginning reading skills using the methodsynthetic structural analysis (SAS)in grade 1 students at Madrasah Ibtidaiyah Negeri 2 Langkat, the implementation is in accordance with the theories that have been used as references. Beginning reading skills using the methodsynthetic structural analysis (SAS)in grade 1 students at Madrasah Ibtidaiyah Negeri 2 Langkat can increase student activity and learning outcomes.